Odpowiedzialność konstytucyjna w Polsce: [Responsibility according to the constitution in Poland] (Studia Prawnicze / The Legal Studies, 1983)
The article discusses the institution of responsibility according to the constitution. It goes back to the 18th century, when constitutional monarchy was being. formed in Poland. The constitution of 1791 defined, for the first time in Europe, the scope of responsibility according to the constitution of ministers and the mode of its realization. Independent Poland accepted this institution as a guarantee of rule of law and introduced it into the Constitution of 1921. In the years. 1918-1939 there were attempts to make use of it but without any practical effects.The legislation of People's Poland considered the institution unnecessary in the conditions of a new political system. Only political and economic crisis reactivated the institution of responsibility according to the constitution. It was introduced by an amendment to the constitution and law on the State Tribunal of March 26, 1982. Its provisions defining subjective and objective scope of responsibility according to the constitution, the mode of its realization and structure of the State Tribunal were analysed in detail. The author points to political prerequisites of solutions, to their advantages and disadvantages. He ends with general remarks on the advantageous functions of the institution in the conditions of the political system and hopes for its practical effectiveness.